Proposed Contract Clauses for Building Information Modelling Integrated Construction Projects - Hansen, Seng; Setiawan, Andre Feliks; Kenrich, (International Journal of Sustainable Construction Engineering and Technology, 2025)
Building Information Modelling (BIM) has been a main approach in modern construction project management due to its abilities in improving efficiency, coordination, and accuracy in all stages of a project lifecycle. Apart from its various benefits, the adoption of BIM technology also presents various contractual problems in construction projects. This study addresses this issue by providing recommended contract clauses that are relevant and contextual for BIM-integrated projects. It employed a context-based mixed-method study approach. First, it identified various contractual issues that occur due to the implementation of BIM technology in construction projects in Indonesia through literature studies and questionnaires. Next, the contract clauses related to these issues were drafted and validated through a two-round Delphi interview with three expert respondents. The results show that contract clauses need to explicitly regulate aspects such as intellectual property rights over BIM, responsibility for data accuracy, etc. This study proposes ten recommended clauses that can be used by practitioners for BIM-integrated projects, namely: definitions, BIM managers, data sharing and exchange, responsibility, project team criteria, intellectual property rights, progress monitoring, security, quality, and costs. These clauses are flexible and applicable for practical use, so that the utilization of BIM technology in construction projects has a clear contractual basis to prevent construction conflicts and disputes. This will encourage a legal ecosystem that supports the optimal and sustainable implementation of BIM in the Indonesian construction sector.